IDENTIFICATION AND QUANTIFICATION OF VERAPAMIL IN BLOOD AND URINE - Georgi Bonchev; Snezha Zlateva; Petko Marinov; Ivelina Stefanova (Peytchinski Publishing, 2020)
Purpose: To adapt and validate an HPLC method for verapamil determination in blood and urine samples. Materials/Methods: Identification of verapamil and its metabolites was made by means of gas-chromatography, using Agilent 7890B/5977A GC-MS system featuring a DB-1701 column. Quantification was done by means of liquid chromatography on Agilent 1260 series HPLC, equipped with Zorbax Extend-C18 column and both diode-array and fluorescent detection modules. Blood and urine specimens were taken from patients of the Clinic for intensive treatment of acute intoxications and toxicoallergies within the course of their treatment. Results: GC-MS identification of verapamil and its metabolites was carried out after simple liquid-liquid extraction of samples without further chemical derivatization. Adapted HPLC method for quantification require isocratic conditions and mobile phase, consisted of phosphate buffer (pH 2.7; 10 mM) containing 1.5 ml L-1 triethylamine - acetonitrile (70:30, v/v) at 20oC, flow-rate 1.0 mL/min and FLD detection (excitation: 203 nm, emission: 320 nm). The method was demonstrated to be linear within the whole region of interest (4.6-4600 ng mL-1) with excellent accuracy (101.7-102.2%) and inter-day precision (5.81%) as well as good analytical recovery (81.2%) and LOQ (7.0 ng mL-1). Conclusion: A precise and easy to use method for verapamil detection and quantification is developed. The method is applicable as a routine procedure in the Laboratory of analytical toxicology for both diagnosis clarification in cases of acute intoxications and therapeutic drug monitoring.